On the Korean optative constructions -essumyen and -kilul from grammaticalisation and pragmatics perspectives - Yae, Sunhee (East Asian Pragmatics, 2022)
Korean has diverse expressions denoting “wishes”. Among them, this paper focuses on the periphrastic constructions of [-essumyen/-kilul + desiderative verbs], excluding the construction [-ko siph-]. Using the perspectives of grammaticalisation and pragmatics, the developmental paths of how the elliptical constructions -essumyen and -kilul realise the concept of the “wish” of the speaker in the optative mood are investigated. This paper will clarify the evolution of the optative markers of -essumyen and -kilul using the mechanisms of grammaticalisation and pragmatic strategies including specialisation, subjectification, intersubjectification, politeness, insubordination, and pragmatic inferences. The SFP (sentential final particle) optatives -essumyen and -kilul take stance-related functions, undergoing insubordination and inviting pragmatic inferences. A corpus analysis will provide usage-based implications of the constructions.